Poor Sleep And Adolescent Obesity Risk: Respiratory Dysfunction [Letter] - Bordoni B (Dove Medical Press, 2019)
Bruno Bordoni Foundation Don Carlo Gnocchi IRCCS, Department of Cardiology, Institute of Hospitalization and Care with Scientific Address, Milan 20100, ItalyCorrespondence: Bruno BordoniFoundation Don Carlo Gnocchi IRCCS, Department of Cardiology, Institute of Hospitalization and Care with Scientific Address, S Maria Nascente, Via Capecelatro 66, Milan 20100, ItalyTel +39 02 3496300617Email bordonibruno@hotmail.comI read with great interest the article by Dr Duraccio and the review on obesity and adolescence. The analysis discussed and the reflections reported are very interesting and relevant.1An aspect that has not been taken into consideration to find reasons for this epidemic of obesity, is the adaptation of the respiratory diaphragm muscle and its systemic relationships.View the original paper by Duraccio and colleagues